2011
DOI: 10.2460/javma.238.12.1629
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of sedation and analgesia in standing horses after administration of xylazine, butorphanol, and subanesthetic doses of ketamine

Abstract: Administration of a subanesthetic dosage of ketamine with xylazine and butorphanol may facilitate certain procedures, such as insertion of a dental float, in horses and enhance tolerance to pressure stimulation, but it may worsen responses to acute pain, such as that caused by a needle prick. Further evaluation is needed to determine whether subanesthetic dosages of ketamine might be useful when performing certain clinical procedures in horses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 14 publications
1
11
0
Order By: Relevance
“…However, the addition of morphine or methadone did not facilitate access to the oral cavity. Similar results were reported with xylazine alone or in combination with butorphanol in standing horses submitted to dental float insertion (WAGNER et al, 2011). In contrast, clinical studies have reported a pronounced degree of sedation and analgesia during standing surgery in horses, with the addition of opioids, such as butorphanol, morphine and buprenorphine, to the α 2 -agonists ( VAN DIJK et al, 2003;BENREDOUANE et al, 2011).…”
Section: Discussionsupporting
confidence: 58%
“…However, the addition of morphine or methadone did not facilitate access to the oral cavity. Similar results were reported with xylazine alone or in combination with butorphanol in standing horses submitted to dental float insertion (WAGNER et al, 2011). In contrast, clinical studies have reported a pronounced degree of sedation and analgesia during standing surgery in horses, with the addition of opioids, such as butorphanol, morphine and buprenorphine, to the α 2 -agonists ( VAN DIJK et al, 2003;BENREDOUANE et al, 2011).…”
Section: Discussionsupporting
confidence: 58%
“…A combination of xylazine, butorphanol and ketamine (0.2 mg/kg bwt i.v. ), relative to xylazine alone or xylazine/butorphanol, did not increase the level of sedation but improved ease of insertion of a dental float, decreased response associated with arthrocentesis and increased pressure algometry threshold at the withers, but increased responsiveness to a sharp needle prick .…”
Section: Management Of Acute Severe Pain: Multimodal Therapymentioning
confidence: 86%
“…Although the majority of work documenting these effects has been performed in other species, ketamine is likely to be most useful in situations where pain is severe or where an individual's pain threshold has been altered such that a previously nonpainful stimulus becomes painful. Antinociception has not been demonstrated in healthy horses receiving infusions of ketamine , but beneficial effects have been noted in clinical settings . A combination of xylazine, butorphanol and ketamine (0.2 mg/kg bwt i.v.…”
Section: Management Of Acute Severe Pain: Multimodal Therapymentioning
confidence: 99%
“…It also contributes to balanced anesthesia by providing intrinsic analgesia during surgery, reduces the drug requirements for maintenance, and enhances recovery during the postoperative period (3,4). Subanesthetic doses of ketamine have been used to provide analgesia in awake and anesthetized horses effectively (5) and to augment sedation along with xylazine and butorphanol in standing anesthesia without any adverse side effects (6). Studies investigating the use of a subanesthetic dose of ketamine at 0.6 mg/kg/h have been shown to enhance analgesia in chronic laminitis (7).…”
Section: Introductionmentioning
confidence: 99%